THERAPEUTIC MANAGEMENT OF CHRONIC KIDNEY DISEASE (CKD) IN CATS - Cavalcante, Átila Bonfim Ferreira; Freitas, Beatriz Silva; Ramos, Paula Rejane Leal Ferreira; Jacinto, Adria Amanda Carvalho; Camillo, Vitoria Cione; Maciel, Laura Gonçalves; Imamura, Júlia Mayumi (Seven Editora, 2026)
Chronic Kidney Disease (CKD) is a highly prevalent condition in felines, especially among geriatric patients. This disease is characterized by progressive evolution and has a multifactorial nature, often associated with comorbidities such as hyperthyroidism. The present study aimed to review and synthesize the main recent scientific evidence regarding the therapeutic management of CKD in cats, with emphasis on nutritional, pharmacological, and diagnostic innovations. This study consists of a narrative literature review conducted in the PubMed database, including articles published in the last five years concerning innovations in the treatment of feline CKD. The research findings demonstrated that nutritional management remains the cornerstone of CKD treatment, particularly in controlling mineral metabolism, highlighting the importance of the calcium:phosphorus ratio and appropriate magnesium supplementation in preventing ionized hypercalcemia. A significant advancement was also observed in the treatment of non-regenerative anemia associated with CKD, with the use of hypoxia-inducible factor prolyl hydroxylase inhibitors, such as molidustat. The gut–kidney axis has also been a promising focus of studies, with the development of strategies aimed at modulating the intestinal microbiota to reduce uremic toxins. Staging according to the guidelines of the International Renal Interest Society (IRIS), and the use of CKD biomarkers such as creatinine and SDMA, are essential for the diagnosis and monitoring of the disease. Finally, it is concluded that modern management of feline CKD must be individualized, integrated, and based on continuous clinical and laboratory monitoring, aiming to slow disease progression, minimize systemic complications, and improve the patient’s quality of life.